Autocontrole do conhecimento de resultados em crianças e adolescentes - Lucas Savassi Figueiredo (2018)
Providing young adults with the opportunity to control feedback requests has proven to be effective in motor skills learning. In children, on the other hand, these results are not observed with the same robustness. Thus, the moment when providing control over feedback becomes efficient for learning is still not well established in the literature. Likewise, the underlying processes that subsidize the effects of self-control in children have also not been properly investigated in previous studies. Thus, the present study sought to investigate the effects of self-controlled feedback in 3 experiments, each with students of different ages (8, 11 and 14 years-old), as well as the relationship between developmental characteristics and the main explanatory hypotheses for the effects of self-control. Therefore, a task of throwing beanbags with the non-dominant arm and occlusion of the vision was used. In each experiment volunteers were allocated into three groups with increasing information processing demands: Yoked (participants received feedback controlled by the experimenter, paired with an individual from the self-controlled condition), Self-controlled (participants were free to request feedback when they judged necessary) and Yoked with self-control (participants could also control the request for feedback, but they should do so within a pre-determined feedback frequency, paired with the subjects in the self-controlled group). In the experiment with 8-year-old children, the selfcontrolled condition was not superior to the externally controlled condition, and the self-controlled condition with restrictions was the worst condition for learning. In the experiment with 11-year-old children, the self-controlled condition was superior to the externally controlled condition, and performance-based feedback request strategies were observed, as it is also observed in young adults. In the experiment with 14year-old adolescents both self-controlled conditions were superior to the externally controlled, with superiority of the Yoked with self-control condition. This result is based on the cognitive resources of adolescents, which were sufficient to deal with the increased demand brought by the self-controlled condition with restrictions. Taken together, the results demonstrated that the effects of self-control seem to be linked to the use of performance-based KR request strategies. In addition, the information processing capabilities seems to act as a limiting factor in obtaining the effects of self-control by children.